Respuesta :
the answer is correct because it would have to go like this;
(-4x + 9)² = (-4x + 9)(-4x + 9)
hope this helps, God bless!
(-4x + 9)² = (-4x + 9)(-4x + 9)
hope this helps, God bless!
Answer:
In fact this equation:
[tex]{(-4x+9)}^{2}[/tex] (1)
Is a perfect square trinomial, which is a polynomial of three terms that results from squaring a binomial (two terms); and the correct way to solve it is:
[tex]{(a+b)}^{2}=a^{2}+2ab+b^{2}[/tex] (2)
Then, according to (2), the binomial (1) is solved as follows:
[tex]{(-4x+9)}^{2}={(-4x)}^{2}+2(-4x)(9)+9^{2}[/tex]
[tex]{(-4x+9)}^{2}=16x^{2}-72x+81[/tex] >>>>>>>This is the righ answer
Therefore, Kylie did not determine the product correctly